Voices of the Arctic: understanding Indigenous securitising moves in the Willow Project, ANWR leases, and the Gállok/Kallak mine - Jamerson, Lindsay (Tartu Ülikool, 2024)
In the last two decades, the Arctic has experienced an increase in extractive industry projects. The resource extraction, motivated by the need for green energy transitions and made easier by global warming, has significantly impacted the security of Indigenous populations occupying their ancestral territory in the Arctic. The Iñupiat, Gwich’in, and Swedish Sami are all actively affected by extractive industry projects in their regions. The Willow Project, the ANWR Leasing Scheme, and the Gállok/Kallak mine, respectively, have become a flashpoint for environmental and political debate and have brought Indigenous perspectives to the forefront of public discourse. This research aimed to determine how Indigenous nations securitised extractive projects and what effect the securitised had on the project’s approval. Using securitisation theory, the speech acts of Indigenous security actors from the three Indigenous nations were collected and analysed to determine if Indigenous security, while using the language of human security, voices the threat of either ontological or societal insecurity. The findings indicate that Indigenous nations construct security threats as ontological or societal threats based on their political and cultural standing but justify the threat at the human security level. https://www.ester.ee/record=b5699147*est